UScale: a digital device for automatic urine volume measurement and frequency volume charting - James Williamson; Tahir Qayyum; Nicolas Bryan; Liam Blunt (Therapeutic Advances in Urology, 2019)
Background: Health issues relating to the lower urinary tract are an increasing burden on the health economy. Measurement of urination frequency/volume using diaries to evaluate symptoms and assess severity is established in the management of these health problems. In current practice, these frequency volume diaries are completed by voiding into a measuring jug and the completion of paper or digital charts. Despite being shown useful to diagnosis, this can be a cumbersome method of data collection, leading to issues with patient compliance. In this paper we describe the established benefits of providing clinicians accurate micturition data followed by an analysis of the problems with the current data collection method. Methods: We introduce our prototype electronic device and accompanying method, which is designed to improve data accuracy and patient compliance, while reducing patient training requirements and clinician workload. Results: The device hardware calibration and testing procedure is described, and two sets of initial data from assumed healthy volunteers are presented, allowing us to demonstrate the advantages of digital data in the fast calculation of diary summary statistics and their potential use to clinicians. Conclusions: We discuss the design improvements to the UScale device, collection bag, and electronic medical records integration undertaken while validating our described method.